Cranial volume and palate length of cats, Felis spp., under domestication, hybridization and in wild populations. Issue 1 (26th January 2022) - Lesch, Raffaela; Kitchener, Andrew C.; Hantke, Georg; Kotrschal, Kurt; Fitch, W. Tecumseh
Abstract : Reduced brain size, compared with wild individuals, is argued to be a key characteristic of domesticated mammal species, and often cited as a key component of a putative 'domestication syndrome'. However, brain size comparisons are often based on old, inaccessible literature and in some cases drew comparisons between domestic animals and wild species that are no longer thought to represent the true progenitor species of the domestic species in question. Here we replicate studies on cranial volumes in domestic cats that were published in the 1960s and 1970s, comparing wildcats, domestic cats and their hybrids. Our data indicate that domestic cats indeed, have smaller cranial volumes (implying smaller brains) relative to both European wildcats ( Felis silvestris ) and the wild ancestors of domestic cats, the African wildcats ( Felis lybica ), verifying older results. We further found that hybrids of domestic cats and European wildcats have cranial volumes that cluster between those of the two parent species. Apart from replicating these studies, we also present new data on palate length in Felis cat skulls, showing that domestic cat palates are shorter than those of European wildcats but longer than those of African wildcats. Our data are relevant to current discussions of the causes and consequences of the 'domestication syndrome' in domesticated mammals.